Integrating Artificial Intelligence and Social Media for English as a Foreign Language (EFL) Learning: A Study on Meta-AI’s Influence on Reading Comprehension - Azmaien, Umme (Journal of Information System and Informatics, 2025)
This study explores the integration of Artificial Intelligence (AI) and social media, particularly Meta-AI-enhanced WhatsApp, in enhancing reading comprehension among English as a Foreign Language (EFL) learners. Despite the growing use of AI and social media in education, there is a notable lack of empirical research examining their combined effect on language learning. To address this gap, a systematic review was conducted following the PRISMA 2020 framework. A total of 850 studies were initially identified from databases such as PubMed, Scopus, Web of Science, and Google Scholar. After applying strict inclusion and exclusion criteria, 140 studies were included in the review, with 20 selected for in-depth analysis. The findings reveal that Meta-AI-supported platforms provide personalized learning paths, adaptive feedback, and enhanced engagement, contributing significantly to the improvement of reading skills. However, challenges such as ethical concerns, reduced human interaction, and technology accessibility were also noted. This study offers valuable insights for educators and policymakers on effectively integrating AI and social media tools into EFL instruction, suggesting that technology-enhanced environments can surpass traditional methods in promoting reading comprehension and learner motivation.